From Taste to Travel: Exploring the Behavioral Drivers of Local Food Engagement and Revisit Intention in Food Tourism - Susanto, Eko (Journal of Tourism, Hospitality and Travel Management, 2023)
Food tourism has become a powerful medium for cultural engagement, destination branding, and sustainable development. This study investigates the behavioral mechanisms underlying tourists' intention to try local food and their revisit intention, with a specific focus on locavore practices in Indonesia. Drawing on the Theory of Planned Behavior and enriched by constructs from experience economy, narrative engagement, and sustainability ethics, a novel conceptual model was developed and tested using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 327 domestic tourists who had engaged in traditional culinary experiences during their travels. The results reveal that perceptions of food authenticity, cultural food attachment, narrative engagement, social media influence, and sustainability awareness significantly influence tourists' intention to try local food. This intention, in turn, strongly predicts revisit intention. Notably, food neophobia was found to negatively moderate the relationship between intention and revisit behavior, underscoring the role of psychological barriers in culinary tourism. The study offers theoretical contributions by integrating underexplored variables into a cohesive behavioral framework and practical implications for tourism stakeholders in designing authentic, inclusive, and sustainability-oriented culinary experiences. These findings highlight the importance of food as both an emotional and ethical medium for enhancing tourist engagement and loyalty in emerging destinations.